Apolonij Rodoški v Katulovi 64. pesmi - Marinčič, Marko (Keria (Ljubljana), 2000)
Catullus' Peleus and Thetis (c. 64) is interpreted in its relation to Apollonius Rhodius and to the tradition of Hellenistic epyllia. In representing his Ariadne as a second Medea, Catullus extended Apollonius' exemplum of Ariadne (Arg. 3,997ff.; 1074ff.; 1096ff,; 4,423ff.) so as to form a digressive parallel story according to the pattern of the epyllia (Moschus' Europa); he replaced Apollonius' ironic ambiguity by a polar opposition between two contrasting images corresponding to a typical pattern of his lyric poems (quondam - nunc). However, the tragic circumstances of Thetis' wedding and the happy outcome of Ariadne's story are suppresed in a way that produces an impression of a complementary whole.
Keywords: antična književnost; Apollonius Rhodius; Catullus, Gaius Valerius; latinska književnost; lirika; literarne študije